Website for E-Promotion in Industry 4.0 - I Budiarti; M Virgin (International Journal of Research and Applied Technology (INJURATECH), 2021)
This study aims to determine the effect of promotion to increase consumers through e-commerce and also the benefits of using e-commerce. In this study, the authors used descriptive method. The results of it were the development of information and communication technology and also internet access create convenience in online business and online shopping, payment system, and promotional activity.